2019
DOI: 10.1111/ene.13877
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency repetitive transcranial magnetic stimulation and intermittent theta‐burst stimulation for spasticity management in secondary progressive multiple sclerosis

Abstract: Background and purpose The spasticity phenomenon is a significant factor in the development of disability. Repetitive transcranial magnetic stimulation (rTMS) is a promising treatment method for this disorder. Our aim was to compare the effects of two protocols of rTMS – the high‐frequency (HF) rTMS (20 Hz) and the intermittent theta‐burst stimulation (iTBS) – on the level of spasticity and concomitant symptoms in patients with secondary progressive multiple sclerosis with an analysis of the duration of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
106
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(130 citation statements)
references
References 17 publications
1
106
0
23
Order By: Relevance
“…iTBS is increasingly being used as a treatment in a range of clinical applications such as rehabilitation, as well as neurological and psychiatric disorders. For example, to promote motor recovery after stroke ( 51 ), for managing spasticity associated with Multiple Sclerosis (MS) ( 52 ), and decreasing obsessive symptomatology associated with Obsessive Compulsive Disorder (OCD) ( 53 ), just to name a few. These protocols all must adhere to the established safety guidelines ( 54 ), and recommendations for clinical TMS use ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…iTBS is increasingly being used as a treatment in a range of clinical applications such as rehabilitation, as well as neurological and psychiatric disorders. For example, to promote motor recovery after stroke ( 51 ), for managing spasticity associated with Multiple Sclerosis (MS) ( 52 ), and decreasing obsessive symptomatology associated with Obsessive Compulsive Disorder (OCD) ( 53 ), just to name a few. These protocols all must adhere to the established safety guidelines ( 54 ), and recommendations for clinical TMS use ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MS-related fatigue, three sham-controlled studies using TMS showed promising results (117)(118)(119). Two of these studies used TMS in combination with physical therapy and enrolled patients affected by spasticity (118,119).…”
Section: Neurophysiology As Innovative Treatment For Fatigue In Ms Pamentioning
confidence: 99%
“…Regarding MS-related fatigue, three sham-controlled studies using TMS showed promising results (117)(118)(119). Two of these studies used TMS in combination with physical therapy and enrolled patients affected by spasticity (118,119). Different TMS protocols were used: intermittent theta-burst stimulation (iTBS) applied to the M1 leg area (119), deep TMS, delivered with specific H-coils to the left prefrontal cortex and to bilateral M1 (117), and 20-Hz repetitive TMS and iTBS applied to bilateral M1 (118).…”
Section: Neurophysiology As Innovative Treatment For Fatigue In Ms Pamentioning
confidence: 99%
See 1 more Smart Citation
“…The postulated pathophysiology of spasticity is that lesions of upper motor neuron impair the supraspinal inhibitory inputs, leading to an increased excitability of α and γ motor neurons, and of the interneurons at the spinal level, ultimately causing spasticity [34,35]. Therefore, facilitatory rTMS and iTBS had been applied to lower spasticity in patients with a number of neurologic disorders [20,33,[36][37][38][39][40][41] by modulating the excitability of cortical motor neurons. In addition, it is increasingly accepted that iTBS may modulate cortical excitability by inducing the long-term potential-like (LTP-like) plasticity changes [10,42,43], and the persistently increasing neural activity may project to inhibitory corticospinal synapses.…”
Section: Discussionmentioning
confidence: 99%